Optimization of Biogas Production from Pineapple Peel Waste (Ananas comosus) through Anaerobic Fermentation with Thermal Pretreatment - Mandasari, Weni -; Prawiranti, Yulizar (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
The increasing global energy demand and depletion of fossil fuel reserves have prompted the search for sustainable energy alternatives. Biogas, produced through anaerobic digestion of organic waste, presents a viable solution. Pineapple peel (Ananas comosus), a major byproduct of Indonesia's fruit processing industry, remains underutilized despite its high lignocellulosic content, which includes cellulose, hemicellulose, and fermentable carbohydrates. This study investigates the potential of pineapple peel as a biogas substrate through a series of pretreatment and anaerobic digestion processes. The peel was thermally pretreated (60–100°C for 25–60 minutes) to enhance biodegradability, then digested with cow manure in a 1:1 ratio under mesophilic conditions (30–37°C) for 30–35 days. Parameters such as TS, VS, BOD, COD, methane yield, pH, and temperature were monitored. Results showed significant reductions in TS, VS, BOD, and COD, indicating efficient organic matter degradation. Methane concentration reached 67.27%, with a biogas yield of 357.19 mL/g VS. FTIR and SEM-EDX analyses confirmed structural breakdown of lignocellulosic bonds, particularly hemicellulose and lignin, enhancing substrate accessibility. The findings demonstrate that pineapple peel, with appropriate pretreatment and co-digestion, is a promising feedstock for sustainable biogas production, offering both environmental and economic benefits in tropical agricultural regions.